Amenore Sekunder pada Remaja dengan Penyakit Ginjal Kronik yang Menjalani Hemodialisis: Laporan Kasus - Muhamad Zaidan Algifari; Shinta Nareswari (CV. Jasa Sukses Abadi, 2026)
Secondary amenorrhea is a reproductive disorder frequently found in female patients with advanced chronic kidney disease (CKD). This condition may be influenced by hormonal dysfunction, malnutrition, anemia, and hemodialysis therapy. We report a 14-year-old female adolescent with stage V CKD who has undergone regular hemodialysis since August 2024 and has experienced secondary amenorrhea for 3 months. She experienced menarche at age 12 and previously had regular menstrual cycles. Physical examination revealed malnutrition (weight 30 kg, height 150 cm). Laboratory examination showed severe anemia with a hemoglobin level of 5.8 g/dL, accompanied by electrolyte disturbances including hyponatremia, hypokalemia, and hypercalcemia. The patient was diagnosed with secondary amenorrhea, stage V CKD, hemodialysis treatment, renal anemia, multiple electrolyte disturbances, and malnutrition. The pathophysiology of amenorrhea in this case is thought to involve a complex interaction between hypothalamic-pituitary-gonadal axis dysfunction induced by uremia, hyperprolactinemia, malnutrition, severe anemia, and the inability of hemodialysis to fully correct neuroendocrine disorders. This case demonstrates the importance of evaluating menstrual disorders in adolescents with advanced CKD. A multidisciplinary approach that includes optimizing dialysis adequacy, improving nutritional status, correcting anemia, and hormonal monitoring is necessary to support reproductive function and improve the patient's quality of life.